Role of Sialyl-O-Acetyltransferase CASD1 on GD2 Ganglioside O-Acetylation in Breast Cancer Cells - Sumeyye Cavdarli; Larissa Schröter; Malena Albers; Anna-Maria Baumann; Dorothée Vicogne; Jean-Marc Le Doussal; Martina Mühlenhoff; Philippe Delannoy; Sophie Groux-Degroote (Cells, 2021)
The O-acetylated form of GD2, almost exclusively expressed in cancerous tissues, is considered to be a promising therapeutic target for neuroectoderm-derived tumors, especially for breast cancer. Our recent data have shown that 9-O-acetylated GD2 (9-OAcGD2) is the major O-acetylated ganglioside species in breast cancer cells. In 2015, Baumann et al. proposed that Cas 1 domain containing 1 (CASD1), which is the only known human sialyl-O-acetyltransferase, plays a role in GD3 O-acetylation. However, the mechanisms of ganglioside O-acetylation remain poorly understood. The aim of this study was to determine the involvement of CASD1 in GD2 O-acetylation in breast cancer. The role of CASD1 in OAcGD2 synthesis was first demonstrated using wild type CHO and CHOΔCasd1 cells as cellular models. Overexpression using plasmid transfection and siRNA strategies was used to modulate CASD1 expression in SUM159PT breast cancer cell line. Our results showed that OAcGD2 expression was reduced in SUM159PT that was transiently depleted for CASD1 expression. Additionally, OAcGD2 expression was increased in SUM159PT cells transiently overexpressing CASD1. The modulation of CASD1 expression using transient transfection strategies provided interesting insights into the role of CASD1 in OAcGD2 and OAcGD3 biosynthesis, and it highlights the importance of further studies on O-acetylation mechanisms.